Heritage in Abdul Wahab Al-Bayati's Divan Collection of Poems: Oriental Texts (Journal of the College of Education for Women, 2019)
Heritage reflects peoples' memory and essence of nations. Thus, this divan was really the material and tool for writers in general and poets in specific both in their artificial innovations . Accordingly, modern writers have endeavored to bring heritage back in all its details and occurrences. Abdullwahab Al-Bayati's experience had reflected his innovative and strong link with the humanitarian heritage, in that heritage in view of Al-Bayati means both the humanitarian expertise and gains that are able to extend from past to future passing through the present.From this, the poet had not disconnected his strong link with the Arab poetic heritage .Thus, the poet had utilized the Arab poetic heritage in expressing on the Arab contrary reality especially in his last poetic divan ( Poetic Texts ) which included poetic texts expressed his dialogues with the heritage symbols and characters ,one of them is Abualallaa Al-Maa'arri , Hafidh Sherazzi , Abu Tammam , Ibn Arabi , and others , as well as mythical symbols, particularly Aisha ( Forouzendah ) in that this universal symbol had dominated Al-Bayati in most collections of poems .This symbol , Aisha ( Forouzendah ) , denotes renewed love or a unified universal power , or as Al-Bayati states about this character as the subjective and collective symbol of love that is unified in one unified soul of existence . In addition, his last poetic divan had linked with many spatial spaces such as Makkah, Damascus , Baghdad , Hawran , Tadmmur , and Bukharah .